Negara, Akreditasi, Dan Hak Atas Pendidikan: Reorientasi Kebijakan Akreditasi Pendidikan Tinggi Di Indonesia - Passiuola, Rezky; Pabubung, Aloysius Aleksander; Pramudya, August Dwi (Publikasi Indonesia, 2025)
This research examines the legal issues surrounding the authority of the Independent Accreditation Agency (Lembaga Akreditasi Mandiri, LAM) in accrediting Study Programs (PS) within higher education institutions, as regulated in Article 55 paragraph (5) of Law No. 12 of 2012 on Higher Education. This provision creates a dualism of authority with the National Accreditation Board for Higher Education (BAN-PT), resulting in a fragmented quality assurance system. The delegation of accreditation authority to LAM without a standardized legal framework potentially obscures the role of the state in ensuring educational quality and generates legal uncertainty, inconsistent standards, and inequality among institutions. This research employs a normative legal method, utilizing statutory and conceptual approaches to analyze the relationship between positive legal norms, scholarly doctrines, and the state’s responsibility in organizing education as a public good. The findings indicate that the legal framework governing LAM contradicts fundamental principles of the rule of law, including substantive justice, equal rights, and public accountability. Education is a constitutional right of every citizen, and its implementation must remain under full state control as a manifestation of the protection and fulfillment of human rights. Therefore, the higher education accreditation system must be integrated under state authority to ensure consistency, quality, and legal certainty in the governance of higher education in Indonesia.